Development of Parking Retribution System with Mobile Application - Nur Sultan Salahuddin; I Wayan Simri; Tirta Paramitta; Trini Septariani (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2013)
A computer based parking retribution system has ever developed before. This system can cover parking retribution system at a building and has been build on web application. But this system just can work in one building, so the Manager just can see the report from the related building. This paper presented the enhancement of parking retribution system. The system will be built on web application and mobile application. This system can be accessed via Internet or mobile application and from the testing, the system give more than 90% true result from all of procedure that have tested